Effect of Different Doses of Nitrogen and Boron on Growth, Yield and Post-Harvest Quality of Broccoli at Rampur, Chitwan - Bhantana, Binod; Giri, Hom Nath; Shrestha, Arjun Kumar; Mishra Tripathi, Kalyani (Journal of Agriculture and Forestry University, 2026)
A field experiment was conducted at Agriculture and Forestry University, Rampur, Chitwan from October 2022 to February 2023 to know the effect of nitrogen and boron on growth, yield, and quality of the Calabrese Variety of broccoli. Four doses of nitrogen as 100, 140, 180, and 220 kg/ha and three doses of boron 1, 1.5, and 2 kg/ha consisting of twelve treatments were applied in RCBD with three replications. Significantly the highest vegetative growth was recorded at 220 kg/ha nitrogen and 2 kg/ha boron dose which was statistically similar to 180 kg/ha nitrogen and 1.5 kg/ha boron dose respectively. The yield of Calabrese broccoli was significantly increased by the increasing rate of N and B application. The highest yield of 14.33 mt/ha was recorded at 220 kg/ha nitrogen which was statistically similar to 180 kg/ha nitrogen dose. Similarly, the highest yield (13.5 mt/ha) of Calabrese broccoli was recorded at 2 kg/ ha boron which was statistically at par to 1.5 kg/ha boron dose. The quality parameters were also found significantly higher at higher doses of nitrogen and boron. The interaction effect of N and B on growth, yield, and quality was found non-significant under the different doses of nitrogen and boron. Nitrogen doses of 180 kg/ha and boron dose of 1.5 kg/ha is recommended for farmers' practice in the Chitwan conditions.